Local and Regional Food Systems: A USDA Priority - Manuel, Virginia (Maine Policy Review, 2011)
Virginia Manuel gives examples of innovative Maine food production, distribution and processing projects and businesses and the ways USDA rural development is financing them.
Keywords: Maine; USDA rural development